2008
DOI: 10.1116/1.3010721
|View full text |Cite
|
Sign up to set email alerts
|

Damage mechanism in low-dielectric (low-k) films during plasma processes

Abstract: Plasma is extensively used for the etching/ashing of low-dielectric (low-k) films. However, since low-k films, such as SiOC films, are vulnerable to plasma irradiation, they are severely damaged during plasma processes, such as the extraction of methyl groups from low-k films. As a result, plasma irradiation increases the dielectric constant of low-k films and reduces the reliability of Cu/low-k interconnects. In previous work, the authors achieved highly selective and low-damage etching processes for low-k fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Jinnai et al 38 suggested that photon irradiation plays an important role in the damage process and enhances the breakage of Si-C bonds. In their study, Ar and SF 6 plasma irradiation was first compared with Ar and SF 6 neutral beam irradiation.…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…Jinnai et al 38 suggested that photon irradiation plays an important role in the damage process and enhances the breakage of Si-C bonds. In their study, Ar and SF 6 plasma irradiation was first compared with Ar and SF 6 neutral beam irradiation.…”
Section: Reliability After Integrationmentioning
confidence: 99%
“…This irradiation often produces charge embedded within dielectrics, which can lead to dielectric damage. 1,2 Typically, the capacitance versus voltage relationship ͑C-V͒ gives us details on the deviation of dielectrics from ideal behavior. 3 This letter shows the relationship between C-V characteristics and the induced charge in organosilicate Si-COH deposited on silicon after VUV/UV irradiation.…”
Section: Effect Of Vacuum Ultraviolet and Ultraviolet Irradiation On mentioning
confidence: 99%
“…9 In addition, the potentially large fluxes of energetic photons, particularly in the VUV range, have been shown to cause a number of unwanted effects, including differential charging of patterned structures, 10 and the creation of bulk and interfacial trap states that contribute to damage induced by leakage currents. 11 Additionally, recent work has reported that plasma exposure can adversely change the mechanical properties of low-k dielectrics, which will worsen dielectric reliability and degrade device performance. 12,13 Our previous work studied the effect of water uptake on the mechanical properties of these low-k dielectrics.…”
Section: Introductionmentioning
confidence: 99%